Factor Structure of the Conflict Tactics Scale 1 - Kaori Baba; Fumie Takauma; Katsuhiko Tada; Tomoko Tanaka; Kyoko Sakanashi; Yaeko Kataoka; Toshinori Kitamura (Shiraz University of Medical Sciences, 2017)
Background: The Conflict Tactics Scale 1 (CTS1) is a widely used self-report measure of abusive attitudes of parents towards children. The factor structure of the CTS1 still remains to be clarified. The aim of this study was to examine the factor structure of the Japanese version of the CTS1 for postpartum women in community settings. Method: The data in this study came from the Okayama and Kumamoto's study. These were part of a larger survey using longitudinal questionnaire studies conducted in Japan from 2001 to 2002 and in 2011, respectively. In both study sites, the participant mothers were asked to fill in the CTS1 one month after delivery when they attended for check-up at the out-patient clinic. Results: A total of 1,150 questionnaires were collected, excluding the participants with missing values in the CTS1. Finally, 1,078 were included in the statistical analyses. Data of 1,078 women were divided into two parts. In the first halved sample (n=578), an exploratory factor analysis was conducted for the CTS1 items after exluding nine items with extremely low prevalence. It revealed 2-factor or 3-factor models. Then, we conducted a model comparison with the second halved sample (n=500), using confirmatory factor analysis. In terms of goodness-of-fit indeces, the 2-factor model was superior. Its subscales were Reasoning and Psycholosical Aggression. Conclusion: The 2-factor model of the CTS1 consisting of Reasoning and Psychological Aggression was superior to the 3-factor model. This is not inconsistent with the original authors' theoretical model.